JUDICIAL INDEPENDENCE IN MODERN LEGAL CONSCIOUSNESS - Горінов, Павло Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The purpose is to reveal the content of the modern legal consciousness of the judicial independence. Methods: institutional and functional independence were identified by means of the comparative method of scientific knowledge, while the use of the classification and grouping method became the methodological basis for the allocation of material and procedural guarantees of independence. The application of a systematic approach made it possible to form a holistic view of the essence of the independence of a judge in modern legal consciousness. Outcomes: The origin of the scientific approach to the modern right of understanding is the recognition of the independence of the judge from the standpoint of his relative autonomy being both an official in the system of judicial authorities and a subject of procedural legal relations during the judicial proceedings. Such a right to an understanding of the judicial independence determined the construction of a system of independence guarantees, which is conventionally subdivided into two subsystems (two types): material and procedural guarantees. The material guarantees are subdivided into sub-groups of organizational guarantees, as well as safeguards addressed to the applicant for a judge’s position or to the judge himself being a bearer of the judiciary. The present paper specifies the connection of procedural guarantees with the realization by a judge of his procedural legal personality in legal relations concerning the administration of justice. Discussion: The author of the article proposes the main provisions that reflect the content of the independence of the judge, based on the legal understanding of his relative autonomy being the subject of the administration of justice and the recognition of material and procedural guarantees of independence.